Pengaruh Tingkat Kebisingan Mesin Kapal terhadap Fungsi Pendengaran dan Stress Kerja pada Teknisi Mesin Kapal - Heru Widada; Alvian Demaz Peramutya; Anicitus Agung Nugroho; Hari Sunanto (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2022)
This study aimed to determine the effect of ship engine noise level on hearing function and work stress on ship engine technicians. The data collection process was carried out within 30 days, from 15 February 2021 to 15 March 2021. This study took a collation at the Merak port of Banten. The method used is a survey using research subjects, ship engine technicians, and the object of research is noise. This study uses primary data in engine maintenance design and the intensity of noise distribution on the ship's engine. The research sample was 2 units of machines with engine criteria aged 1 year and 6 years. The equipment used in this study is a sound level meter, an object to measure the noise that has been calibrated. This research uses the descriptive analysis method. The results showed that the noise value at full rpm was 70.3-104 dB (A) and 59.2-77.5 dB (A) when in a stationary state. Referring to the data, the age of the machine does not affect the noise level. As a preventive measure against something that can become an obstacle regarding noise on board, it is necessary to use ear protection devices such as ear protection devices called earplugs. Noise can be minimized by regularly lubricating the engine and installing silencers to prevent sound from spreading to other rooms so that it can reduce the risk due to noise that causes stress, headaches, high blood pressure and other diseases